Flexible drought deciduousness in a neotropical understory herb. Issue 8 (25th August 2022) - Harenčár, Julia G.; Ávila‐Lovera, Eleinis; Goldsmith, Gregory R.; Chen, Grace F.; Kay, Kathleen M.
Abstract: Premise: Adaptive divergence across environmental gradients is a key driver of speciation. Precipitation seasonality gradients are common in the tropics, yet drought adaptation is nearly unexplored in neotropical understory herbs. Here, we examined two recently diverged neotropical spiral gingers, one adapted to seasonal drought and one reliant on perennial water, to uncover the basis of drought adaptation. Methods: We combined ecophysiological trait measurements in the field and greenhouse with experimental and observational assessments of real‐time drought response to determine how Costus villosissimus (Costaceae) differs from C. allenii to achieve drought adaptation. Results: We found that drought‐adapted C. villosissimus has several characteristics indicating flexible dehydration avoidance via semi‐drought‐deciduousness and a fast economic strategy. Although the two species do not differ in water‐use efficiency, C. villosissimus has a more rapid growth rate, lower leaf mass per area, lower stem density, higher leaf nitrogen, and a strong trend of greater light‐saturated photosynthetic rates. These fast economic strategy traits align with both field‐based observations and experimental dry‐down results. During drought, C. villosissimus displays facultative drought‐deciduousness, losing lower leaves during the dry season and rapidly growing new leaves in the wet season. Conclusions: We revealed a drought adaptation strategy that has not, to our knowledge, previously been documented in tropical herbs. This divergent drought adaptation evolved recently and is an important component of reproductive isolation between C. villosissimus and C. allenii, indicating that adaptive shifts to survive seasonal drought may be an underappreciated axis of neotropical understory plant diversification. Abstract : Resumen en Español: Premisa del estudio: La divergencia adaptativa a lo largo de gradientes ambientales es un factor clave de la especiación. Los gradientes de estacionalidad de la precipitación son comunes en los trópicos, sin embargo, la adaptación a la sequía es casi inexplorada en las hierbas neotropicales del sotobosque. Examinamos dos especies de caña agria neotropicales que divergieron recientemente, uno adaptado a la sequía estacional y otro que depende del agua perenne, para descubrir la base de la adaptación a la sequía. Métodos: Combinamos mediciones ecofisiológicas en el campo y el invernadero con una evaluación experimental y observacional de la respuesta a la sequía en tiempo real para determinar cómo Costus villosissimus (Costaceae) difiere de C. allenii para lograr la adaptación a la sequía. Resultados clave: Encontramos que C. villosissimus, que está adaptado a la sequía, tiene varias características que indican que evita la deshidratación a través de la caducididad y una estrategia de vida rápida. Aunque las dos especies no difieren en la eficiencia del uso del agua, C. villosissimus tiene una tasa de crecimiento más rápida, menor masa foliar por área, menor densidad del tallo, mayor nitrógeno foliar y una fuerte tendencia de mayores tasas fotosintéticas saturadas de luz. Estos atributos de la estrategia de vida rápida se alinean tanto con las observaciones basadas en el campo como con los resultados experimentales de sequía. Para sobrevivir a la sequía, C. villosissimus es caducifolia facultativa, perdiendo hojas inferiores durante la estación seca y creciendo rápidamente hojas nuevas en la estación húmeda. Conclusiones: Revelamos una estrategia de adaptación a la sequía que, hasta donde sabemos, no ha sido documentada previamente en hierbas tropicales. Esta adaptación divergente a la sequía evolucionó recientemente y es un componente importante del aislamiento reproductivo entre C. villosissimus y C. allenii, lo que indica que los cambios adaptativos para sobrevivir a la sequía estacional pueden ser un eje subestimado de la diversificación de las plantas del sotobosque neotropical.